2022
DOI: 10.1007/s11606-022-07587-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Firearm Access Among Post-9/11 US Women Veterans Using Reproductive Healthcare: a Cross-Sectional Survey

Abstract: Background Suicide rates have increased among women Veterans, with increased use of firearms as the method. Addressing suicide risk in this population requires understanding the prevalence and correlates of firearm access in healthcare settings frequented by women Veterans. Objectives Characterize the prevalence and correlates of firearm ownership and storage practices among women Veterans using Department of Veterans Affairs (VA) reproductive healthcare (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…As such guidance was not mandated at the time of data collection, it is possible that women Veterans' firearm access and beliefs have changed since then, particularly for those who have used VHA services (data indicate, however, that only 14% of those using VHA services recall ever having a conversation with a provider about firearms [67]). Additionally, considering the prevalence of military sexual trauma in this sample, as well as in other studies of women Veterans with firearm access [51], a trauma-informed approach to firearm discussions with women Veterans may be particularly important [53,56]. This may entail carefully attending to power differentials in the context of such discussions, clearly communicating the rationale for firearm questions and recommendations, and approaching firearm-related conversations collaboratively [68].…”
Section: Plos Onementioning
confidence: 87%
See 1 more Smart Citation
“…As such guidance was not mandated at the time of data collection, it is possible that women Veterans' firearm access and beliefs have changed since then, particularly for those who have used VHA services (data indicate, however, that only 14% of those using VHA services recall ever having a conversation with a provider about firearms [67]). Additionally, considering the prevalence of military sexual trauma in this sample, as well as in other studies of women Veterans with firearm access [51], a trauma-informed approach to firearm discussions with women Veterans may be particularly important [53,56]. This may entail carefully attending to power differentials in the context of such discussions, clearly communicating the rationale for firearm questions and recommendations, and approaching firearm-related conversations collaboratively [68].…”
Section: Plos Onementioning
confidence: 87%
“…However, in research conducted with women Veterans prior to the pandemic, sexual assault during military service appeared to precipitate women Veterans' firearm acquisition and firearm storage (e.g., keeping firearms easily accessible) following their military service [50]. Military sexual harassment has also been associated with increased prevalence of household firearm access among women Veterans [51]. The present findings add to this knowledge base by suggesting that post-9/11 women Veterans who experience military sexual trauma (specifically, sexual assault) have a higher prevalence of changed beliefs regarding firearms and a higher prevalence of engagement in firearm behaviors during the COVID-19 pandemic, relative to women Veterans who have not experienced military sexual harassment or assault.…”
Section: Plos Onementioning
confidence: 99%
“…Cleveland and colleagues found that Veteran women were less likely than Veteran men to personally own firearms (24.4% vs. 47.2%, respectively), but more likely to report living in households with firearms that they did not personally own (14.4% vs. 2.2%) (Cleveland et al 2017 ). Subsequent surveys with post-9/11 women Veterans also reported a high prevalence of personal and household firearm ownership among women Veterans (Monteith et al 2022b , Monteith et al 2023 ). Further, a qualitative study highlighted the prominent role of spouses and partners of women Veterans in household firearm access (Monteith et al 2020 )—findings which converge with survey-based findings in which married women Veterans reported a higher prevalence of living in a household with firearms owned by someone else (Monteith et al 2022b ).…”
Section: Introductionmentioning
confidence: 97%
“…17,18 Recently, firearm marketing campaigns have targeted women in this vein, with slogans like "God Created Man and Woman, But Samuel Colt Made Them Equal." 21 At the individual level, though, evidence regarding associations between personal experiences of violence and gun ownership or gun carrying is mixed, [22][23][24][25][26] with positive associations found between experiencing violence and firearm carrying behavior among youths. 22,23,[27][28][29][30] An understanding of how lasting the effects of violent experiences are on gun access has been hindered by a lack of longitudinal, individual-level data on firearms.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of gun owners who cite personal protection as a primary motivation for ownership has grown from 48% to 76% over the past 2 decades, signaling a growing public acceptance of firearms as an appropriate and empowering strategy to address fear of external violence. 17 , 18 Recently, firearm marketing campaigns have targeted women in this vein, with slogans like “God Created Man and Woman, But Samuel Colt Made Them Equal.” 21 At the individual level, though, evidence regarding associations between personal experiences of violence and gun ownership or gun carrying is mixed, 22 , 23 , 24 , 25 , 26 with positive associations found between experiencing violence and firearm carrying behavior among youths. 22 , 23 , 27 , 28 , 29 , 30 An understanding of how lasting the effects of violent experiences are on gun access has been hindered by a lack of longitudinal, individual-level data on firearms.…”
Section: Introductionmentioning
confidence: 99%